The changing village environment in Southeast Asia : applied anthropology and environmental reclamation in the northern Philippines - Wallace, Ben J., 1937- (Modern anthropology of South-East Asia., 2006)
This book follows the work of the 'Good Roots Project' - a multi-year forestry and agriculture research project in the Philippines. The scheme is an attempt on the part of industry, science and the government to better understand the processes of deforestation and initiate a strategy by which stressed upland ecosystems can be returned to productive stability. This comparative study aims quite simply, to help the farmers of the island to help themselves. Ben Wallace the director of the study investigates the issues surrounding the project, how the initiatives have been implemented, and.